Modulation of the innate immune response, antioxidant system and oxidative stress during acute and chronic stress in pacu (Piaractus mesopotamicus) - de Fátima Pereira de Faria, Camila [UNESP]; dos Reis Martinez, Claudia Bueno; Takahashi, Leonardo Susumu [UNESP]; de Mello, Mariana Maluli Marinho [UNESP]; Martins, Talísia Pereira [UNESP]; Urbinati, Elisabeth Criscuolo [UNESP] (Springer Nature, 2021)
Stress is an energy-demanding process, as well as the responses of the innate immune system, that impose a metabolic overload on cellular energy production, which can affect the cellular redox balance, causing oxidative damage. We evaluated the role of stress in the modulation of innate immune and oxidative/antioxidant mechanisms in juvenile pacu exposed to acute and chronic stressors. The experimental period lasted 30 days, and fish (113.7 ± 35.1 g) were fed commercial feed. During this period, half of the fish were not manipulated (Condition A), and the other half were chased with a dip net for 5 min twice a day (Condition C). After the 30-day period, fish from both groups were sampled (baseline sampling), and the remainders (not sampled) were air exposed for 3 min (acute stressor), returned to the tanks, and were sampled again 30 min, 3 h, 6 h, and 24 h after air exposure. We evaluated biomarkers of stress (circulating cortisol and glucose), the innate immune system (respiratory burst activity/RBA, hemolytic activity of the complement system (HA-AP) and serum concentration of lysozyme), oxidative damage (lipid peroxidation/LPO), and antioxidant enzymes (superoxide dismutase, SOD; catalase, CAT; and glutathione peroxidase, GSH-Px). Our results showed that stress, acutely or chronically, caused a transient reduction of RAL and activated the HA-AP. Acutely, stress increased the lysozyme concentration. Furthermore, both conditions caused oxidative stress in the liver, and differently they modulated the antioxidant system, enhancing SOD activity and impairing CAT and GSH-Px activity.
Keywords: Cellular redox; Cortisol; Fish farming; Immunity; Reactive oxygen species